2017
DOI: 10.1038/s41467-017-01695-x
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial metabolic engineering using an orthogonal tri-functional CRISPR system

Abstract: Designing an optimal microbial cell factory often requires overexpression, knock-down, and knock-out of multiple gene targets. Unfortunately, such rewiring of cellular metabolism is often carried out sequentially and with low throughput. Here, we report a combinatorial metabolic engineering strategy based on an orthogonal tri-functional CRISPR system that combines transcriptional activation, transcriptional interference, and gene deletion (CRISPR-AID) in the yeast Saccharomyces cerevisiae. This strategy enable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
259
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 260 publications
(262 citation statements)
references
References 56 publications
2
259
1
Order By: Relevance
“…Orthogonal dCas9 (SpdCas9 and SadCas9) have been used for complex and inducible gene transcription control (Y. Gao et al, ) as well as for simultaneous imaging of multiple genomic loci (Chen et al, ). More recently, a trifunctional CRISPR system that combines 3 orthogonal Cas9 variants was developed for simultaneous gene activation (using LbdCas12a), repression (using SpdCas9) and deletion (using SaCas9) in the yeast Saccharomyces cerevisiae (Lian, HamediRad, Hu, & Zhao, ). However, to the best of our knowledge, no other studies have reported the use of multiple Cas9 orthologs for metabolic engineering of E. coli .…”
Section: Discussionmentioning
confidence: 99%
“…Orthogonal dCas9 (SpdCas9 and SadCas9) have been used for complex and inducible gene transcription control (Y. Gao et al, ) as well as for simultaneous imaging of multiple genomic loci (Chen et al, ). More recently, a trifunctional CRISPR system that combines 3 orthogonal Cas9 variants was developed for simultaneous gene activation (using LbdCas12a), repression (using SpdCas9) and deletion (using SaCas9) in the yeast Saccharomyces cerevisiae (Lian, HamediRad, Hu, & Zhao, ). However, to the best of our knowledge, no other studies have reported the use of multiple Cas9 orthologs for metabolic engineering of E. coli .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, microbial production of pseudoionone using metabolic engineering and synthetic biology approaches (Lian et al . , ; Wang et al . ) have attracted increasing attention.…”
Section: Discussionmentioning
confidence: 99%
“…However, the supply of biologically synthesized pseudoionone is largely limited by their low concentration in nature. Therefore, microbial production of pseudoionone using metabolic engineering and synthetic biology approaches (Lian et al 2017(Lian et al , 2018Wang et al 2018) have attracted increasing attention.…”
Section: Discussionmentioning
confidence: 99%
“…As metabolic engineering often requires synergistic regulation of multiple genes, combinational strategies is highly desirable. Recently, an orthogonal trifunctional CRISPR system combines transcriptional activation, transcriptional interference, and gene deletion (CRISPR‐AID) was developed in S. cerevisiae . Three independent CRISPR proteins with different PAM sequences and gRNA scaffolds were combined in this system.…”
Section: Crispr‐based Genome Engineeringmentioning
confidence: 99%